Quadrilateral extensions

Geometry Level pending

The sides A D AD and B C BC of a convex quadrilateral A B C D ABCD are extended to meet at E E . Let H H and G G be the midpoints of B D BD and A C AC , respectively. Find the ratio of the area of the triangle E H G EHG to that of the quadrilateral A B C D ABCD .


The answer is 0.25.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

We place the configuration on a coordinate system, so that point E E is at the origin and points A A and B B lie on the positive x x -axis. Let A ( a , 0 ) A\left( a,0 \right) , B ( b , 0 ) B\left( b,0 \right) and C ( c , d ) C\left( c,d \right) . Then we have E A = ( a , 0 ) E B = ( b , 0 ) E C = ( c , d ) \overrightarrow{EA}=\left( a,0 \right) \ \ \ \ \ \overrightarrow{EB}=\left( b,0 \right) \ \ \ \ \ \overrightarrow{EC}=\left( c,d \right) Since E C \overrightarrow{EC} and E D \overrightarrow{ED} have the same direction, there exists a positive number p p , such that E D = p E C \overrightarrow{ED}=p\overrightarrow{EC} , i.e. E D = ( p c , p d ) \overrightarrow{ED}=\left( pc,pd \right)

Moreover, G is the midpoint of A C G ( a + c 2 , d 2 ) G\text{ is the midpoint of }AC\Leftrightarrow G\left( \dfrac{a+c}{2},\dfrac{d}{2} \right) H is the midpoint of B D H ( b + p c 2 , p d 2 ) H\text{ is the midpoint of }BD\Leftrightarrow H\left( \dfrac{b+pc}{2},\dfrac{pd}{2} \right) Now we proceed to the calculation of the areas. [ A B C D ] = [ E A D ] [ E B C ] = 1 2 det ( E A , E D ) 1 2 det ( E B , E C ) = 1 2 a 0 p c p d 1 2 b 0 c d = 1 2 a p d 1 2 b d \begin{aligned} \left[ ABCD \right] & =\left[ EAD \right]-\left[ EBC \right] \\ & =\frac{1}{2}\left| \det \left( \overrightarrow{EA},\overrightarrow{ED} \right) \right|-\frac{1}{2}\left| \det \left( \overrightarrow{EB},\overrightarrow{EC} \right) \right| \\ & =\frac{1}{2}\left| \left| \begin{matrix} a & 0 \\ pc & pd \\ \end{matrix} \right| \right|-\frac{1}{2}\left| \left| \begin{matrix} b & 0 \\ c & d \\ \end{matrix} \right| \right| \\ & =\frac{1}{2}\left| apd \right|-\frac{1}{2}\left| bd \right| \\ \end{aligned} We notice that a a , b b , p p , d d are all positive numbers, thus [ A B C D ] = 1 2 ( a p d b d ) ( 1 ) \left[ ABCD \right]=\frac{1}{2}\left( apd-bd \right) \ \ \ \ \ (1) For E H G \triangle EHG , [ E H G ] = 1 2 det ( E G , E H ) = 1 2 a + c 2 d 2 b + p c 2 p d 2 = 1 8 a p d b d \begin{aligned} & \left[ EHG \right]=\dfrac{1}{2}\left| \det \left( \overrightarrow{EG},\overrightarrow{EH} \right) \right| \\ & =\dfrac{1}{2}\left| \left| \begin{matrix} \dfrac{a+c}{2} & \dfrac{d}{2} \\ \dfrac{b+pc}{2} & \dfrac{pd}{2} \\ \end{matrix} \right| \right| \\ & =\dfrac{1}{8}\left| apd-bd \right| \\ \end{aligned} But, a > b > 0 a>b>0 , p > 1 p>1 and d > 0 d>0 imply that a p d > b d apd>bd , thus, [ E H G ] = 1 8 ( a p d b d ) ( 2 ) \left[ EHG \right]=\dfrac{1}{8}\left( apd-bd \right) \ \ \ \ \ (2) Finally, ( 1 ) , ( 2 ) [ E H G ] [ A B C D ] = 1 8 ( a p d b d ) 1 2 ( a p d b d ) = 1 4 = 0.25 \left( 1 \right),\left( 2 \right)\Rightarrow \dfrac{\left[ EHG \right]}{\left[ ABCD \right]}=\dfrac{\dfrac{1}{8}\left( apd-bd \right)}{\dfrac{1}{2}\left( apd-bd \right)}=\dfrac{1}{4}=\boxed{0.25} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...